Analysing Literary Discourse: Implications for Literary Translation - Lotfipour-Saedi, Kazem (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1992)
AbstractThis paper will attempt to look at the notion of translation equivalence in literary discourse. Literature is usually distinguished from non-literature in terms of the special effect it creates on the reader. The paper will try to characterize this “special effect” in terms of special discoursal and textual strategies employed in literary text. It will then examine ways of rendering such strategies in the translation process drawing implications for the issue of translatability in literature.